Seems tough....But its Real Easy !!

If a + b = 2015 a+b=2015 , where a a and b b are natural numbers, then what is the value of

( 1 ) a + ( 1 ) b = ? { (-1) }^{ a }+{ (-1) }^{ b }=?

2015 -2 2 0

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Mishal Sheik
Jan 8, 2016

W e k n o w t h a t , O d d + E v e n = O d d T h e n d e f i n i t e l y , a m u s t b e o d d & b m u s t b e e v e n ( O R ) a m u s t b e e v e n & b m u s t b e o d d L e t u s t a k e , a i s o d d a n d b i s e v e n T h e n , ( 1 ) o d d t i m e s + ( 1 ) e v e n t i m e s ( 1 ) + 1 = 0 We\quad know\quad that,\quad Odd+Even=Odd\\ \\ Then\quad definitely,\quad a\quad must\quad be\quad odd\quad \& \quad b\quad must\quad be\quad even\quad (OR)\quad a\quad must\quad be\quad even\quad \& \quad b\quad must\quad be\quad odd\\ \\ Let\quad us\quad take,\quad a\quad is\quad odd\quad and\quad b\quad is\quad even\quad \\ Then,\\ \quad \quad \quad \quad \quad \quad { (-1) }^{ odd\quad times }+{ (-1) }^{ even\quad times }\\ \quad \quad \quad \quad \quad (-1)+1\quad =0

It should be specified that a,b are natural numbers

Santosh Narva - 5 years, 5 months ago

Log in to reply

Ok.....thank you...I'll edit it

Mishal Sheik - 5 years, 5 months ago
Kay Xspre
Jan 13, 2016

An alternating way to solve this is to view b = 2015 a b = 2015-a , then we will get ( 1 ) a + ( 1 ) 2015 ( 1 ) a = ( 1 ) a ( 1 1 ) 2015 = ( 1 ) a ( 1 ) a = 0 (-1)^a+\frac{(-1)^{2015}}{(-1)^a} = (-1)^a-(\frac{1}{-1})^{2015} = (-1)^a-(-1)^a = 0

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...